Religion in International Relations Theory: Understanding the Role of Religion in International Relations (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Religion has been an important factor in interstate relations during the ancient civilizations. Friendship, hostility, war and peace between states were always determined by religious values. After the Peace Treaty of Westphalia in 1648, nation-states came into existence, religion was subjected to international relations and was supposed to be removed from internal state politics. With the Peace Treaties of Westphalia, which led to the foundation of nation-states, and international politics, these nation states have moved towards secularism. Even though religion has been exasperated to be theoretically underdeveloped in historical developments, it has always played an important role in international relations in practice. Therefore, to reveal the place and influence of religion in international relations or global politics, it is necessary to talk about the relation of religion and secularism. Religion has begun to manifest itself in international politics with the terrorist acts that started in the last epoch of the Cold War and the transboundary effect of terror. After the events of September 11, 2001, religion has attracted the attention of international relations scholars and statesmen. The perceptions of religion in international relations after 2001 and the academic studies discussed in this field mostly refer to religion as an ideology. The study of the ideologies of terrorist organizations such as the Taliban, ISIS, and Al-Qaeda, as if it had dealt with the religion of Islam, is nothing less than a contempt for Islamism, which is reductionism, against the idea of millions of people who believe in religion. This disdain applies to other religions too. Still, religion has no place in the theory of international relations. It is very difficult to address religion within the framework of current theories of international relations. Because religion and the theories of international relations are in contradiction. In order to deal with the theories of religion in the context of international relations, a scientific revolution is required in the theories of this discipline as expressed by Thomas Kuhn.